Guinea : Staff Report for the 2002 Article IV Consultation, the First Review Under the Poverty Reduction and Growth Facility, Requests for Waiver of Performance Criteria, Second-Year Program Under the Poverty Reduction and Growth Facility, and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report, 2004)
The first review of the three-year PRGF arrangement approved on May 2, 2001, has been delayed to give the authorities time to rectify weaknesses in program execution during a four-month consolidation period by meeting specified revenue and expenditure targets set for that period. The medium-term macroeconomic framework underpinning the poverty reduction strategy paper is consistent with that of the initial poverty reduction growth facility (PRGF)-supported program approved. The public enterprise restructuring and privatization program remains a key element of the structural reform agenda.